THE PROBLEMATIC OF THE RISE OF BROUGHT IN PRIVATE COMPANY WORKFORCE RECRUITMENT AND ITS LEGAL ANALYSIS - Anita Dwi Lestari; Imam Budi Santoso (Universitas Labuhanbatu, 2024)
Job vacancies that can't accommodate the number of applicants and the problems that occur with the increase of brokers in job recruitment became a posh interest discuss. With numerous cases regarding this brokering, there are still few or maybe rare ones who bring it up in journal writings. Although this discussion is highly relevant to raised in published papers, especially within the realm of law, job seekers are often more careful in following the selection process for recruiting workers. This writing uses descriptive-analytical and empirical methods to corroborate the paper supported the particular situation supported by the legal elaboration. This case is regarding brokering never expected because it disturbed and harmed job seekers regarding the proper to urge employment through equity and justice. The applicable legal umbrella should be ready to protect it. Not only tied to the corporate but also has ranged from the recruitment process. Legal certainty is required as prohibitions and sanctions. No more brokers can handle legal certainty, which is necessary as prohibitions and sanctions. As a result, no more brokers can take ad legal certainty. It required embargoes and sanctions so that no more brokers could cash in on things. Keywords: brokers; Company; private; Labor.